BARRIERS AND FACILITATORS TO PROVIDING MENTAL HEALTH CARE WITHIN PALLIATIVE CARE. (11th November 2018) - Kozlov, E; Reid, C
Abstract: Palliative care (PC) is interdisciplinary care that improves the quality of life for patients with serious illness and their families by addressing physical, psychological, practical and spiritual issues. Though psychological care is a core component of PC, it is unclear what psychological interventions are being provided to address palliative care patients' mental health needs. In a national survey of 243 palliative care providers from multiple disciplines, barriers and facilitators to providing mental health care were assessed. Key barriers included lack of time (46%), limited resources for mental health referrals (42%), and patients' unwillingness or resistance to discussing psychological distress (39%). Key facilitators included availability of psychosocial staff to accept referrals (45%), more training in how to identify and treat psychological distress (37%), more time (51%), and technology to assist in the management of mental health symptoms (48%). In order to deliver palliative care that includes optimally addressing patients' mental health needs, systems, researchers and clinicians need to take into account solutions to overcoming key barriers identified in this study as well as opportunities to enhance the facilitators.